2016
DOI: 10.1016/j.eucr.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ureteropelvic Junction Obstruction Secondary to Metastatic Relapse of Breast Cancer

Abstract: We describe the case of a 53-year-old woman with a history of localized breast cancer who presented with flank pain and was found to have new-onset obstruction of the left ureteropelvic junction. Although initially believed to be unrelated to her history of prior malignancy, intraoperative assessment of tissue from the ureteropelvic junction during planned laparoscopic pyeloplasty revealed urothelial infiltration by carcinoma of breast origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Naranji et al ( 4 ) reported a case of right-sided UPJ obstruction in a 78-year-old woman who underwent laparoscopic pyeloplasty that showed mantle cell lymphoma on final histology. The only reported observation of malignant infiltration of the UPJ by a solid organ cancer is a case of recurrent breast cancer reported by Shah et al ( 3 ) in 2016. Importantly, to the best of our knowledge, this case report is the first to describe metastasis of a primary biliary tract malignancy to the UPJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naranji et al ( 4 ) reported a case of right-sided UPJ obstruction in a 78-year-old woman who underwent laparoscopic pyeloplasty that showed mantle cell lymphoma on final histology. The only reported observation of malignant infiltration of the UPJ by a solid organ cancer is a case of recurrent breast cancer reported by Shah et al ( 3 ) in 2016. Importantly, to the best of our knowledge, this case report is the first to describe metastasis of a primary biliary tract malignancy to the UPJ.…”
Section: Discussionmentioning
confidence: 99%
“…Although most commonly observed in pediatric populations, UPJ obstruction in adults can arise from a number of etiologies, including congenital causes, acquired stenosis due to urolithiasis, urothelial malignancy, and other retroperitoneal disease processes (1,2). Intraluminal malignant obstruction due to metastatic involvement of the UPJ, however, is exceedingly rare, with few case reports existing in the literature (3,4). Herein we describe the case of a patient with a history of hilar cholangiocarcinoma treated with a liver transplant, whose systemic recurrence presented as an isolated right UPJ obstruction six years later.…”
Section: Introductionmentioning
confidence: 99%